HIV Prevention and Treatment Behavior Change and the Situated Information Motivation Behavioral Skills (sIMB) Model: A Qualitative Evaluation of a Community Health Worker Intervention in Rakai, Uganda. - Pollard, Rose; Kennedy, Caitlin E.; Hutton, Heidi E.; Mulamba, Jeremiah; Mbabali, Ismail; Anok, Aggrey; Nakyanjo, Neema; Chang, Larry W.; Amico, K. Rivet (AIDS & Behavior, 2022)
A community health worker (CHW) model can promote HIV prevention and treatment behaviors, especially in highly mobile populations. In a fishing community in Rakai, Uganda, the Rakai Health Sciences Program implemented a CHW HIV intervention called Health Scouts. The situated Information, Motivation, and Behavioral Skills (sIMB) framework informed the design and a qualitative evaluation of the intervention. We interviewed 51 intervention clients and coded transcripts informed by sIMB framework dimensions. Clients reported that Health Scouts provided information about HIV prevention and treatment behaviors and helped them manage personal and social motivations to carry out health-promoting behavior. Prominent barriers which moved clients away from behavior change included daily pill burdens, anticipated stigma, serostatus disclosure, substance use at social gatherings, and anticipated reactions of partners. Our study adds to the evidence establishing CHWs as facilitators of behavior change, positioned to offer supportive encouragement and navigate contextualized circumstances.